РУССКО-ПОЛЬСКИЕ ОНОМАСИОЛОГИЧЕСКИЕ СООТВЕТСТВИЯ В СФЕРЕ НАЗВАНИЙ ЖИВОТНЫХ - Jóźwiak, Jolanta (Studia Rossica Posnaniensia, 2008)
The aim of the article is to present the onomasiological relationships between paired equivalents of Russian and Polish animal names. These pairs have been grouped in two categories, depending on the type of the relationship between them: complete onomasiological identity or complete onomasiological difference.